1984
DOI: 10.3171/jns.1984.60.6.1269
|View full text |Cite
|
Sign up to set email alerts
|

Failure of tetracaine to reverse spinal cord injury in the cat

Abstract: Beginning 30 minutes after acute spinal cord injury, cats were treated by the administration of continuous spinal anesthesia for 8 hours. This was achieved by the intermittent injection of hyperbaric tetracaine into the subarachnoid space at the site of injury via an indwelling catheter. There were no significant differences in functional recovery or histologically assessed tissue preservation between treated cats and concurrently managed control animals. The indwelling subarachnoid catheter used for drug admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In vivo studies have shown that intravenous lidocaine offered little or at best modest protection against cerebral ischemia (Gelb et aI., 1988;Evans et aI., 1989;Sutherland et aI., 1989;Rasool et aI., 1990;Dutka et at., 1992). The benefit of local anes thetics in spinal cord injury models is likewise mod est (Ford and Maim, 1984;Kobrine et aI., 1984;Haghighi et aI., 1987). However, very few of the many available Na + channel-blocking agents have been tested in vivo, and it appears that the degree of protection versus suppression of excitability in nor mal tissue varies widely from compound to com pound.…”
Section: Antiarrhythmics Protect By Reducing Na + Influxmentioning
confidence: 99%
“…In vivo studies have shown that intravenous lidocaine offered little or at best modest protection against cerebral ischemia (Gelb et aI., 1988;Evans et aI., 1989;Sutherland et aI., 1989;Rasool et aI., 1990;Dutka et at., 1992). The benefit of local anes thetics in spinal cord injury models is likewise mod est (Ford and Maim, 1984;Kobrine et aI., 1984;Haghighi et aI., 1987). However, very few of the many available Na + channel-blocking agents have been tested in vivo, and it appears that the degree of protection versus suppression of excitability in nor mal tissue varies widely from compound to com pound.…”
Section: Antiarrhythmics Protect By Reducing Na + Influxmentioning
confidence: 99%